High-performance composite polyurethane plastic comprehensive material and preparation method thereof
By combining the polyurethane components and polyurea components, a complex hydrogen bond structure and micro-phase separation structure is formed, the problem of insufficient tensile strength of existing polyurethane plastic materials is solved, and the high performance composite polyurethane plastic composites is achieved Meeting tensile strength and high-end demand.
Patent Information
- Application Number
- CN202411609304.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
The tensile strength of existing polyurethane plastic materials is limited and cannot fully meet high-end needs.
High-performance composite polyurethane plastic composite is used to form a complex mesh hydrogen bond structure and micro-phase separation structure by combining the polyurethane components and polyurea components, thereby improving the tensile strength of the material.
High tensile strength is achieved, which can fully meet high-end needs, and further improve the performance of the material through preferred fillers and additives.
Smart Images

Figure BDA0005130531900000071 
Figure BDA0005130531900000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polyurethane, and more specifically, to a high-performance composite polyurethane plastic composite material and a preparation method thereof. Background Art
[0002] Polyurethane plastics are widely used in various sports venues, such as running tracks and stadiums. The principle is to form a high molecular weight network structure polymer through the reaction of isocyanate groups and hydroxyl groups, thereby giving the product excellent physical properties. This material not only improves the safety and comfort of ground facilities, but also has a long service life and relatively low maintenance costs, which can significantly improve the sports experience and safety. Common polyurethane plastics can be divided into two main types: single-component and two-component. The raw materials of two-component polyurethane plastics include prepolymers containing isocyanate groups (material A) and slurries containing a variety of additives and fillers (material B).
[0003] In the related art, there is a polyurethane track, which is prepared according to the following method: (1) Weigh a polyurethane prepolymer as material A and set it aside; mix polyether polyol and chlorinated paraffin, stir and heat to 70-75°C, add a chain extender, continue to heat to 100-110°C, and after the chain extender is completely melted, add an antioxidant, red iron oxide, fumed silica and heavy calcium in sequence, stir and disperse at 100-105°C for 30 minutes, and then vacuum dehydrate for 2 hours, then cool the material to below 40°C, continue to stir and disperse for 30 minutes, and then pour out to obtain material B; (2) Mix material A and material B in a weight ratio of 1:5, add a gel catalyst, use a high-speed disperser to stir evenly, and then vacuum degas, then pour the mixture into a mold and place it for curing to complete the preparation of the plastic track.
[0004] With respect to the above-mentioned related technologies, the inventors believe that the polyurethane plastic materials in the related technologies are limited by the inherent properties of isocyanate groups and hydroxyl groups, and it is difficult to achieve high tensile strength. There are certain limitations in practical applications and they cannot fully meet high-end demands. Summary of the invention
[0005] In the related art, the tensile strength of polyurethane plastic materials is limited and cannot fully meet high-end requirements. In order to improve this defect, the present application provides a high-performance composite polyurethane plastic composite material and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-performance composite polyurethane plastic composite material, adopting the following technical scheme: a high-performance composite polyurethane plastic composite material, comprising a polyurethane component and a polyurea component, the weight of the polyurethane component accounting for 50-90% of the total weight of the composite material, the polyurethane component is compounded by material A and material B, the material A is a polyurethane prepolymer, the NCO value of the polyurethane prepolymer is 4-12%, the components of the material B include polyether polyol, catalyst, antioxidant, anti-ultraviolet agent and filler; the polyurea component includes a polyurea prepolymer with an NCO value of 13-15%.
[0007] By adopting the above technical scheme, the present application uses polyurethane component and polyurea component for compounding, and obtains high-performance composite polyurethane plastic composite material. The carbamate group in the polyurethane component and the urea group in the polyurea component can both be used as proton donors for hydrogen bonds, and the carbonyl group in the polyurethane and polyurea and the ether group in the polyurethane soft segment can both be used as proton acceptors for hydrogen bonds. Under the synergistic cooperation of these groups, a complex network hydrogen bond structure can be generated in the composite polyurethane plastic composite material of the present application, and the formation of hydrogen bonds provides sufficient driving force for the composite polyurethane plastic composite material to form a microphase separation structure. The plastic micro-region formed during the microphase separation process can be connected to the soft segment as a connection point on the one hand, and can enhance the soft segment region on the other hand. The presence of a large number of plastic micro-regions avoids stress concentration. When the extended crack encounters the plastic micro-region, the plastic micro-region consumes a large amount of energy through plastic deformation, causing the crack to bifurcate or change direction, thereby dispersing the stress inside the material, improving the stress state of the stressed sample, and increasing the tensile strength of the material, so that the high-performance composite polyurethane plastic composite material can fully meet high-end needs.
[0008] Preferably, the polyurethane prepolymer is prepared according to the following method: The polyether polyol is subjected to vacuum dehydration, and then the polyether polyol is mixed with isocyanate and reacted under heating conditions to obtain a polyurethane prepolymer after the reaction is completed.
[0009] By adopting the above technical solution, vacuum dehydration can reduce the interference of moisture in the polyether polyol on the reaction, which is helpful to achieve the stable preparation of composite polyurethane plastic composite materials.
[0010] Preferably, the polyurethane prepolymer is prepared at a temperature of 80-100°C.
[0011] By adopting the above technical solution, the temperature of 80-100° C. can make the polyether polyol and the isocyanate fully react, which is helpful to obtain a polyurethane prepolymer with an NCO value within the target range.
[0012] Preferably, the water content of the polyether polyol after vacuum dehydration is 300-500 ppm.
[0013] By adopting the above technical solution, within the range of 300-500 ppm, the water content in the polyether polyol has little effect on the reaction, while further reducing the water content will further increase the cost.
[0014] Preferably, the polyurea component is prepared as follows: (1) under nitrogen protection, dissolving isocyanate in DMF solvent, stirring at a constant temperature, and adding amino polyether to obtain a polyurea prepolymer; (2) Adding a chain extender and an amino polyether to the prepolymer and the polyurea to obtain a polyurea component.
[0015] By adopting the above technical solution, the present application uses isocyanate and amino polyether to synthesize a polyurea prepolymer, and then further adds a chain extender and amino polyether to react to obtain a polyurea component. Since the present application is to compound the polyurethane component with the polyurea component, the chain extender in the polyurea component also serves as a chain extender for the polyurethane. Similarly, various additives in the polyurethane component can also act on the polyurea component, thereby achieving an organic combination of the polyurea component and the polyurethane component.
[0016] Preferably, the chain extender is a diamine chain extender, and the diamine chain extender is MOCA.
[0017] By adopting the above technical solution, there are four active hydrogens in the MOCA molecule. The urea group formed by the chain extension reaction of MOCA can form a double coordination hydrogen bond, which is conducive to the microphase separation between the soft and hard segments, and can promote the aggregation of the hard segments to form microcrystals, thereby playing the role of a cross-linking point, which helps to fully improve the tensile strength of the composite polyurethane plastic material.
[0018] Preferably, the filler includes modified wood fibers, and the modified wood fibers are prepared according to the following method: bisphenol A liquid epoxy resin and dicyandiamide are dissolved in methanol to obtain a modified liquid, the wood fibers are immersed in the modified liquid, the wood fibers are taken out after standing, and the wood fibers are baked to obtain modified wood fibers.
[0019] By adopting the above technical solution, the present application obtains modified wood fiber by coating wood fiber with epoxy resin, and uses the modified wood fiber as filler. The modified wood fiber can be used as a reinforcing phase of a composite polyurethane plastic composite material, and the coating of epoxy resin fully overcomes the defect of poor compatibility of wood fiber with polyurethane and polyurea materials, so the modified wood fiber can effectively transmit and disperse stress, thereby fully improving the tensile strength of the composite polyurethane plastic composite material.
[0020] Preferably, the filler further comprises alkali lignin, and the number average molecular weight of the alkali lignin is 750-950.
[0021] By adopting the above technical scheme, the present application also selects alkali lignin of a specific molecular weight and modified wood fiber as a reinforcing phase. Within the range selected in the present application, the hydroxyl groups on the surface of the alkali lignin can participate in the formation of a hydrogen bond network structure, thereby improving the bonding effect between polyurethane, polyurea and the reinforcing phase. In addition, the rigid structure of the alkali lignin has a certain effect on improving the tensile strength, thereby being able to obtain a composite polyurethane plastic composite material with higher tensile strength.
[0022] Preferably, the filler comprises nano-microcrystalline cellulose, and the nano-microcrystalline cellulose is prepared according to the following method: (1) crushing waste paper into shredded paper strips for later use; adding sodium hydroxide, hydrogen peroxide, sodium silicate, a surfactant, and an emulsifier into water to dissolve to obtain a deinking agent for later use; (2) adding the shredded paper strips into a deinking agent and soaking them, stirring, dispersing and washing them with water to obtain pulp, and crushing the pulp to obtain waste paper fibers; (3) Mixing waste paper fibers with sulfuric acid and heating them in a constant temperature water bath, then adding ice water to terminate the reaction, and obtaining nano-microcrystalline cellulose after filtration and washing.
[0023] By adopting the above technical solution, the present application further selects nano-microcrystalline cellulose made from waste paper as a reinforcing phase based on modified wood fiber and alkali lignin. This nano-microcrystalline cellulose has a high degree of crystallinity, can use hydrogen bonds and covalent bonds to induce the soft segment phase and hard segment phase of the composite polyurethane plastic composite material to be arranged regularly, and reinforce the soft segment phase and hard segment phase, thereby improving the material performance and increasing the tensile strength of the material.
[0024] In a second aspect, the present application provides a method for preparing a high-performance composite polyurethane plastic composite material, using the following technical solution.
[0025] A method for preparing a high-performance composite polyurethane plastic composite material comprises the following steps: (1) mixing material A and material B and stirring them evenly, grinding them to obtain a polyurethane component for later use; preparing a polyurea prepolymer, and then further processing the polyurea prepolymer into a polyurea component for later use; (2) The polyurethane component and the polyurea component are mixed, stirred, and then poured into a mold for curing to obtain a high-performance composite polyurethane plastic material.
[0026] By adopting the above technical solution, the present application prepares a polyurethane component and a polyurea component respectively, then mixes the two components, and performs mold curing to obtain a high-performance composite polyurethane plastic composite material. The high-performance composite polyurethane plastic composite material of the present application has better tensile properties than conventional polyurethane plastic materials, and can fully meet high-end needs.
[0027] In summary, this application has the following beneficial effects: 1. The present application uses a polyurethane component and a polyurea component for compounding to obtain a high-performance composite polyurethane plastic complex. The high-performance composite polyurethane plastic complex of the present application can overcome the limitations of the inherent properties of isocyanate groups and hydroxyl groups, achieve higher tensile strength, and fully meet high-end needs.
[0028] 2. In the present application, MOCA is preferably used as the chain extender for polyurethane prepolymer and polyurea prepolymer. There are four active hydrogens in the MOCA molecule. The urea group formed after the chain extension reaction can form a double coordination hydrogen bond, which is beneficial to the microphase separation between the soft and hard segments, and can promote the aggregation of the hard segments to form microcrystals, thereby playing the role of a cross-linking point, which helps to fully improve the tensile strength of the composite polyurethane plastic material.
[0029] 3. The present application uses modified wood fiber, alkali lignin and nano-microcrystalline cellulose as reinforcing phases, which fully improves the tensile strength of the composite polyurethane plastic composite material. In addition, the nano-microcrystalline cellulose is made of waste paper, which fully realizes the recycling of waste. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0031] Preparation example of modified wood fiber The following is an explanation using Preparation Example 1.
[0032] Preparation Example 1 In this preparation example, the modified wood fiber was prepared according to the following method: E-51 epoxy resin and dicyandiamide were weighed in a weight ratio of 100:11, and then the E-51 epoxy resin and dicyandiamide were dissolved in methanol to obtain a modified liquid with a mass fraction of 2 wt% of E-51 epoxy resin. Wood fibers (average diameter of 5 μm, average length of 1 mm) dried at 80°C for 6 hours were immersed in the modified liquid, and the wood fibers were taken out after standing for 3 hours, and then the wood fibers were baked at 100°C for 1 hour, and then dried at 80°C for 8 hours to obtain modified wood fibers.
[0033] Preparation example of nanocrystalline cellulose The following is an explanation using Preparation Example 2.
[0034] Preparation Example 2 In this preparation example, nanocrystalline cellulose was prepared according to the following method: (1) crushing waste paper into shredded paper strips for later use; adding sodium hydroxide (1.5 wt%), hydrogen peroxide (3 wt%), sodium silicate (5 wt%), a surfactant (1.5 wt%), and an emulsifier (1.5 wt%) into water and dissolving them to obtain a deinking agent for later use; in this step, the surfactant is SDBS and the emulsifier is OP-10; (2) adding the shredded paper strips into a deinking agent and soaking them for 30 minutes, stirring and dispersing them at 10,000 r / min for 15 minutes, washing them with water to obtain pulp, and crushing the pulp to obtain waste paper fibers; (3) Waste paper fibers were mixed with 59 wt % sulfuric acid at a ratio of 2 g:100 mL, heated in a constant temperature water bath at 45° C. for 1 h, and then 10 times the volume of ice water was added to terminate the reaction. After 1 h, the mixture was filtered and washed to obtain nano-microcrystalline cellulose. Example
[0035] Examples 1-5 The following description is given by taking Example 1 as an example.
[0036] Example 1 The present embodiment provides a high-performance composite polyurethane plastic composite material, including a polyurethane component and a polyurea component, the weight of the polyurethane component accounts for 90% of the total weight of the composite material, the polyurethane component is compounded by material A and material B, material A is a polyurethane prepolymer, the NCO value of the polyurethane prepolymer is 4%, and the components of material B include polyether polyol, catalyst, antioxidant, anti-ultraviolet agent and filler; the polyether polyol is polyoxypropylene glycol (PPG, Mn=2000), the molar ratio between the hydroxyl group of the polyether polyol and the NCO group in the polyurethane prepolymer is 1.1:1; the catalyst is dibutyltin dilaurate, and the amount of the catalyst accounts for 1.5% of the total weight of the composite material. The antioxidant is antioxidant 1010, and the amount of the antioxidant is 0.3% of the total weight of the comprehensive material; the anti-ultraviolet agent is UV1164, and the amount of the anti-ultraviolet agent is 0.5% of the total weight of the comprehensive material; the filler is heavy calcium powder, and the amount of the filler is 10% of the total weight of the comprehensive material; the polyurea component includes a polyurea prepolymer with an NCO value of 13%, a chain extender and an amino polyether, the chain extender is ethylenediamine, and the chain extender coefficient is 0.8 (taking into account the NCO groups in the polyurethane component and the polyurea component), the specification of the amino polyether is ED600, and the ratio between the amino group in the amino polyether and the NCO group in the polyurea prepolymer is 1.1:1.
[0037] This embodiment provides a method for preparing a high-performance composite polyurethane plastic composite material, comprising the following steps: (1) vacuum dehydrating polyether polyol to obtain polyether polyol with a water content of 500 ppm (abbreviated as water content in Table 1), then mixing polyether polyol with isocyanate, reacting under heating conditions of 80° C. (abbreviated as T in Table 1), and obtaining a polyurethane prepolymer with an NCO value of 4% after the reaction, taking the polyurethane prepolymer as material A, mixing material A with material B, stirring evenly, grinding to obtain a polyurethane component, and setting aside; dissolving isocyanate in DMF solvent under nitrogen protection, stirring at a constant temperature of 10° C., and adding amino polyether, and obtaining a polyurea prepolymer with an NCO value of 13% after the reaction; adding a chain extender and amino polyether to the prepolymer and polyurea to obtain a polyurea component, and setting aside; (2) The polyurethane component and the polyurea component are mixed, stirred, and then poured into a mold for curing to obtain a high-performance composite polyurethane plastic material.
[0038] As shown in Table 1, the differences between Examples 1-5 mainly lie in the mass fractions of the polyurethane component and the polyurea component (referred to as the polyurethane ratio and the polyurea ratio), as well as some different production and processing parameters.
[0039] Table 1 Polyurethane proportion, polyurea proportion and some production and processing parameters sample Example 1 Example 2 Example 3 Example 4 Example 5 Polyurethane ratio / % 90 80 70 60 50 Polyurea proportion / % 10 20 30 40 50 NCO value of polyurethane prepolymer / % 4 7 10 11 12 NCO value of polyurea prepolymer / % 13 13.6 14 14.3 15 Moisture content / % 500 450 400 350 300 T / ℃ 80 85 90 95 100 Example 6 The difference between this embodiment and embodiment 5 is that the chain extender is replaced by MOCA.
[0040] Example 7 The difference between this embodiment and embodiment 6 is that the filler is composed of heavy calcium powder and plant source filler in a weight ratio of 1:1, and the plant source filler is the wood fiber of preparation example 1.
[0041] Example 8 The difference between this embodiment and embodiment 7 is that the plant-derived filler is composed of the wood fiber of preparation example 1 and alkali lignin having a number average molecular weight of 600 in a weight ratio of 1:1.
[0042] Example 9 The difference between this embodiment and embodiment 8 is that the number average molecular weight of the alkali lignin is 750.
[0043] Example 10 The difference between this embodiment and embodiment 8 is that the number average molecular weight of the alkali lignin is 850.
[0044] Embodiment 11 The difference between this embodiment and embodiment 8 is that the number average molecular weight of the alkali lignin is 950.
[0045] Example 12 The difference between this example and Example 11 is that the plant-based filler is composed of the wood fiber of Preparation Example 1, alkali lignin with a number average molecular weight of 950, and nano-microcrystalline cellulose of Preparation Example 2 in a weight ratio of 1:1.
[0046] Comparative Example Comparative Example 1 In this comparative example, material B is a commercially available polyurethane prepolymer with a specification of YJ2011-B.
[0047] A polyurethane runway is prepared according to the following method: (1) Weigh the polyurethane prepolymer of Example 1 as material A for later use; add 140g EP-330N, 60g DL-2000D and 200g 52# medium-chain chlorinated paraffin into a three-necked flask, stir and heat to 75°C, add 20g chain extender 1,4-butanediol, continue to heat to 105°C, and after MOCA is completely melted, add 5g antioxidant 1010, 10g red iron oxide, 15g fumed silica and 5g heavy calcium in sequence, stir and disperse at 105°C for 30min, then start the vacuum pump and vacuum dehydrate for 2h (keeping the pressure below -0.09MPa); cool the material to below 40°C, continue to stir and disperse for 30min, then pour out, thus completing the preparation of material B; (2) Mix material A and material B in a weight ratio of 1:5, add gel catalyst PC-03, use a high-speed disperser to stir at 2000r / min for 20s, stir evenly and perform vacuum degassing, then pour the mixture into a mold and let it solidify to complete the preparation of the plastic track.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that the polyurea component is removed based on the formulation of Example 1.
[0049] Comparative Example 3 The difference between this comparative example and Example 1 is that, based on the formula of Example 1, the polyurea prepolymer and the amino polyether are removed, and only the chain extender component is retained.
[0050] Performance testing methods The tensile properties of the material were measured on a universal material testing machine, with a tensile rate of 100 mm / min at room temperature, a load of 10 kg, a sample length of 120 mm, a width of 4 mm, and a thickness of about 1 mm. The data was taken as the average value of 5 tests, and the operation was performed with reference to the standard "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" (GB / T 528-2009). After the results were measured, the ratio between the tensile strength of each embodiment and the comparative example and the tensile strength of the comparative example 1 was calculated based on the results of the comparative example 1, and the ratio was recorded as the relative tensile strength. The results are shown in Table 2.
[0051] Table 2 Relative tensile strength It can be seen from Examples 1-5 and Comparative Example 1 and Table 2 that the relative tensile strengths measured in Examples 1-5 are all higher than those in Comparative Example 1, indicating that the present application has fully overcome the limitations of the inherent properties of isocyanate groups and hydroxyl groups by compounding the polyurethane component and the polyurea component, and obtained a high-performance composite polyurethane plastic composite material, achieving a higher tensile strength and being able to fully meet high-end needs.
[0052] Combining Example 1 and Comparative Example 2 and Tables 2-3, it can be seen that the relative tensile strength measured in Example 1 is significantly higher than that in Comparative Examples 2-3, indicating that in the absence of polyurethane prepolymer and amino polyether, the samples of Comparative Examples 2-3 cannot achieve higher tensile strength.
[0053] Combining Example 5 and Example 6 with Table 2, it can be seen that the relative tensile strength measured in Example 6 is higher than that in Example 5. This is because there are four active hydrogens in the MOCA molecule, and the urea group formed after the chain extension reaction can form a double coordination hydrogen bond, which is beneficial to the microphase separation between the soft and hard segments, and can promote the aggregation of the hard segments to form microcrystals, thereby playing the role of a cross-linking point, which helps to fully improve the tensile strength of the composite polyurethane plastic composite material.
[0054] Combining Example 6 and Example 7 with Table 2, it can be seen that the relative tensile strength measured in Example 7 is higher than that in Example 6. This is because the modified wood fiber can be used as a reinforcing phase of the composite polyurethane plastic composite material, and the epoxy resin coating fully overcomes the defect of poor compatibility between the wood fiber and the polyurethane and polyurea materials. Therefore, the modified wood fiber can effectively transfer and disperse stress, thereby fully improving the tensile strength of the composite polyurethane plastic composite material.
[0055] Combining Example 7, Example 8-11 and Table 2, it can be seen that the relative tensile strength measured in Example 8-11 is higher than that in Example 7. This is because the hydroxyl groups on the surface of the alkali lignin can participate in the formation of the hydrogen bond network structure, thereby improving the bonding effect between the polyurethane, polyurea and the reinforcing phase, and the rigid structure of the alkali lignin has a certain effect on the tensile strength, so that a composite polyurethane plastic composite material with higher tensile strength can be obtained. According to the data in Table 2, it can be further seen that when the number average molecular weight of the alkali lignin is 750-950, the tensile strength of the composite polyurethane plastic composite material is higher.
[0056] Combining Example 11, Example 12 and Table 2, it can be seen that the relative tensile strength measured in Example 12 is higher than that in Example 11. This is because the nano-microcrystalline cellulose can use hydrogen bonds and covalent bonds to induce the soft segment phase and the hard segment phase of the composite polyurethane plastic composite material to be arranged regularly, and reinforce the soft segment phase and the hard segment phase, thereby improving the material performance and increasing the tensile strength of the material.
[0057] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A high-performance composite polyurethane plastic composite material, characterized in that: The invention comprises a polyurethane component and a polyurea component, wherein the weight of the polyurethane component accounts for 50-90% of the total weight of the composite material, and the polyurethane component is compounded by material A and material B, wherein material A is a polyurethane prepolymer, and the NCO value of the polyurethane prepolymer is 4-12%, and the components of material B include polyether polyol, catalyst, antioxidant, anti-ultraviolet agent and filler; and the polyurea component includes a polyurea prepolymer with an NCO value of 13-15%.
2. The high-performance composite polyurethane plastic composite material according to claim 1, characterized in that: The polyurethane prepolymer is prepared according to the following method: The polyether polyol is subjected to vacuum dehydration, and then the polyether polyol is mixed with isocyanate and reacted under heating conditions to obtain a polyurethane prepolymer after the reaction is completed.
3. The high-performance composite polyurethane plastic composite material according to claim 2, characterized in that: The polyurethane prepolymer is prepared at a temperature of 80-100°C.
4. The high-performance composite polyurethane plastic composite material according to claim 3, characterized in that: The water content of the polyether polyol after vacuum dehydration is 300-500ppm.
5. The high-performance composite polyurethane plastic composite material according to claim 1, characterized in that: The polyurea component is prepared as follows: (1) Under nitrogen protection, isocyanate is dissolved in DMF solvent, stirred at a constant temperature, and amino polyether is added to obtain a polyurea prepolymer; (2) Adding a chain extender and an amino polyether to the prepolymer and the polyurea to obtain a polyurea component.
6. The high-performance composite polyurethane plastic composite material according to claim 5, characterized in that: The chain extender is a diamine chain extender, and the diamine chain extender is MOCA.
7. The high-performance composite polyurethane plastic composite material according to claim 6, characterized in that: The filler comprises modified wood fiber, and the modified wood fiber is prepared according to the following method: Bisphenol A type liquid epoxy resin and dicyandiamide are dissolved in methanol to obtain a modified liquid, wood fiber is immersed in the modified liquid, the wood fiber is taken out after standing, and the wood fiber is baked to obtain modified wood fiber.
8. The high-performance composite polyurethane plastic composite material according to claim 7, characterized in that: The filler further comprises alkali lignin, and the number average molecular weight of the alkali lignin is 750-950.
9. The high-performance composite polyurethane plastic composite material according to claim 8, characterized in that: The filler comprises nano-microcrystalline cellulose, and the nano-microcrystalline cellulose is prepared according to the following method: (1) Crush the waste paper into shredded paper strips for later use; add sodium hydroxide, hydrogen peroxide, sodium silicate, a surfactant, and an emulsifier into water and dissolve them to obtain a deinking agent for later use; (2) adding the shredded paper strips into a deinking agent and soaking them, stirring, dispersing and washing them with water to obtain pulp, and then crushing the pulp to obtain waste paper fibers; (3) Mixing waste paper fibers with sulfuric acid and heating them in a constant temperature water bath, then adding ice water to terminate the reaction, and obtaining nano-microcrystalline cellulose after filtration and washing.
10. The method for preparing a high-performance composite polyurethane plastic composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Mixing material A and material B, stirring them evenly, grinding them to obtain a polyurethane component, which is set aside; preparing a polyurea prepolymer, and then further processing the polyurea prepolymer into a polyurea component, which is set aside; (2) The polyurethane component and the polyurea component are mixed, stirred, and then poured into a mold for curing to obtain a high-performance composite polyurethane plastic material.